Catalisadores sólidos superácidos à base de sílica-alumina, zeólita HY e óxido de cério (IV) sulfatado para produção de biodiesel - Fernandes, Débora da Silva Maculan (2018)
Based on a increasing need to reduce biodiesel production costs, this study aimed at evaluating the catalytic activity of different solid superacid catalysts (zeolite HY (HY), HY with 5% sulfur cerium (IV) oxide (SO4 2-/CeO2) (HY5), HY with 10% SO4 2-/CeO2 (HY10), silica alumina (Siral 30), Siral 30 with 5% SO4 2-/CeO2 (S5), Siral 30 with 10% SO4 2-/CeO2 (S10)) in the in the esterification reaction of oleic acid with methanol for the production of methyl oleate, one of the main components of biodiesel. The catalysts were characterized by Thermogravimetric analysis (TG/DrTG), Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD) and adsorption/desorption of N2. The effects of the independent variables were evaluated using a 2 3 factorial design. The variables were: temperature, molar ratio (oleic acid/methanol) and percentage of catalyst, their interactions on the dependent variable, and percentage of oleic acid to methyl oleate conversion. The characterizations allowed the identification of changes in the catalysts when compared to the starting materials. The ideal temperature for the heat treatment of the catalysts was found by TG/DrTG. The FTIR spectra confirmed that the proposed modifications occurred in the composites. DRX showed a decrease in crystallinity of HY and the change from Siral 30 from amorphous to crystalline with the insertion of SO4 2-/CeO2. N2 adsorption and desorption isotherms confirmed the presence of micropores in HY, HY5 and HY10 and mesoporos in Siral 30, S5 and S10. For most of the evaluated catalysts, the optimum reaction parameters were obtained with lower percentage of catalyst (2%), higher temperatures (100 °C) and low (1:5) (oleic acid/methanol) molar ratio. The maximum conversions obtained were: 83.2% HY5, 68.8% S10, 68.5% S5, 66,9% Siral 30, 63.9% HY10, and 45.3% zeolite HY. Based on the results, the synthesized catalysts were shown to be promising for biodiesel production through the oleic acid esterification and methanol